Study on Unnatural Death Patterns in Dhaka City - Khan, Md Belayet Hossain; Hossain, Md Mosharraf (Anwer Khan Modern Medical College Journal, 2011)
Unnatural deaths are the deaths which are caused by any means other than any disease1. Unnatural death is an indicator of social and mental health. This retrospective study was done to ascertain the pattern of unnatural deaths, whose autopsies were performed by Forensic medicine dept. of Dhaka Medical College from 1st Jan, 1996 to 31st Dec, 2000. A total 10436 death recorded were analysed to see their age, sex etc. The study revealed that total number of unnatural deaths were 9413, out of them males were higher than females ( M- 75.78% & F- 24.22%). Results showed that Accidental deaths were 77.22%, Homicidal deaths were 14.02% and Suicidal deaths were 10.76%. Accidental & Homicidal deaths were more common in male, whereas suicidal deaths were more common in female. This study suggest an extensive studies to formulate strategies to prevent those unnatural death to improve the situation. Key Words: Unnatural Death Patterns; Suicidal; Accidental DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8167 AKMMC J 2011; 2(2): 18-20